Aesthetic and cultural study of the Indoculinire logo - Dwi Ramayanti (Deskomvis: Jurnal Ilmiah Desain Komunikasi Visual, Seni Rupa dan Media, 2025)
This study aims to examine the aesthetic and cultural values ​​of the Indoculinaire logo, which represents a brand identity that embodies Indonesian culinary heritage. The first focus of this study is design elements such as color, typography, illustration, and composition. Second, the logo's principles are simplicity, product description, effectiveness in black and white, and clarity when the logo is reduced in size. Third, the brand embodies cultural aesthetic values. The research method used was qualitative with a descriptive-interpretive approach. Data were obtained using observation, interviews, documentation, and literature studies. In practice, interviews and observations were conducted in a complementary manner. The results show that the Indoculinaire logo embodies cultural aesthetic values, with a spirit of preserving and sustaining Indonesian culinary diversity. The design elements and logo principles applied to the logo create a modern impression without eliminating cultural values. The conclusion of this study is that Indoculinaire is a brand capable of representing a modern and cultured identity. This study demonstrates that the application of cultural aesthetics in brand identity design, particularly logos, is crucial in strengthening brand values ​​based on local wisdom.